Does an Overdraft Facility Influence the Customer Costs of Using a Personal Current Account?. Issue 1 (2nd January 2017) - Ashton, John K.; Gregoriou, Andros
Abstract: This study examines whether personal current accounts offering an overdraft facility cost customers less to use than accounts not offering this service. This analysis uses a UK data set of 222 personal current accounts, recorded monthly between 1995 and 2011, in combination with interest rates from 1200 instant-access deposit accounts offered contemporaneously by the same firms. Our results indicate personal current accounts offering overdraft facilities have higher deposit and payment service costs than accounts not offering this service. The finding is robust to varying service attributes. This result is inconsistent with suggestions that overdraft users have been cross-subsidising other personal current account users as widely reported in theoretical and policy literatures. It is concluded that implicit and inertia costs of personal current account use may be more influential than previously reported in the pricing of these accounts.